Food Justice: Access, Equity, and Sustainability for Healthy Students and Communities. (1st October 2016) - Roselle, René; Connery, Chelsea
Abstract: Describing how food insecurity is a threat to our country's democratic health and student success, the authors bring the issue of food justice into focus using the inequities in Hartford, Connecticut, and the ways one organization is working toward solutions .